Analysis of longitudinal variations in North Pacific alkalinity to improve predictive algorithms. Issue 10 (15th October 2016) - Fry, Claudia H.; Tyrrell, Toby; Achterberg, Eric P.
Abstract: The causes of natural variation in alkalinity in the North Pacific surface ocean need to be investigated to understand the carbon cycle and to improve predictive algorithms. We used GLODAPv2 to test hypotheses on the causes of three longitudinal phenomena in Alk*, a tracer of calcium carbonate cycling. These phenomena are (a) an increase from east to west between 45°N and 55°N, (b) an increase from west to east between 25°N and 40°N, and (c) a minor increase from west to east in the equatorial upwelling region. Between 45°N and 55°N, Alk* is higher on the western than on the eastern side, and this is associated with denser isopycnals with higher Alk* lying at shallower depths. Between 25°N and 40°N, upwelling along the North American continental shelf causes higher Alk* in the east. Along the equator, a strong east‐west trend was not observed, even though the upwelling on the eastern side of the basin is more intense, because the water brought to the surface is not high in Alk*. We created two algorithms to predict alkalinity, one for the entire Pacific Ocean north of 30°S and one for the eastern margin. The Pacific Ocean algorithm is more accurate than the commonly used algorithm published by Lee et al. (2006), of similar accuracy to the best previously published algorithm by Sasse et al. (2013), and is less biased with longitude than other algorithms in the subpolar North Pacific. Our eastern margin algorithm is more accurate than previously published algorithms. Key Points: Longitudinal variations in alkalinity in the North Pacific are influenced by physical processes Predictive algorithms for alkalinity are improved by using indicators of physical processes